2011
DOI: 10.1091/mbc.e10-11-0893
|View full text |Cite
|
Sign up to set email alerts
|

The LC3 recruitment mechanism is separate from Atg9L1-dependent membrane formation in the autophagic response againstSalmonella

Abstract: When Salmonella invade mammalian epithelial cells, some populations are surrounded by the autophagy protein LC3. We found that LC3 was recruited in proximity to Salmonella independently of both Atg9L1 and FIP200, which are required for formation of autophagosomes. The dynamics of the ULK1 complex and Atg9L1 were dependent on one another.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
207
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 159 publications
(221 citation statements)
references
References 52 publications
(87 reference statements)
12
207
1
1
Order By: Relevance
“…Such apparently normal recruitment of LC3B to S . Typhimurium in cells failing to restrict bacterial proliferation (Fig 1A and C) may be due to conjugation of LC3 to the remnants of SCV membranes rather than anti‐bacterial phagophores, a phenotype well‐documented for MEFs with defects in upstream autophagy components such as FIP200 or ATG9 (Kageyama et al , 2011). The phenotype in Tbk1 −/− MEFs therefore points to an upstream defect in the autophagy pathway.…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations
“…Such apparently normal recruitment of LC3B to S . Typhimurium in cells failing to restrict bacterial proliferation (Fig 1A and C) may be due to conjugation of LC3 to the remnants of SCV membranes rather than anti‐bacterial phagophores, a phenotype well‐documented for MEFs with defects in upstream autophagy components such as FIP200 or ATG9 (Kageyama et al , 2011). The phenotype in Tbk1 −/− MEFs therefore points to an upstream defect in the autophagy pathway.…”
Section: Resultsmentioning
confidence: 78%
“…Since wortmannin, a potent inhibitor of VPS34, prevents colocalization of WIPI1 but not LC3 with S . Typhimurium (Kageyama et al , 2011), we tested whether TBK1 was similarly required for the recruitment of WIPI proteins to bacteria. We found that GFP‐tagged WIPI1 and WIPI2B but not WIPI3 and WIPI4 accumulated on S .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The group led by Sharon Tooze has shown that Atg9 partially colocalizes with recycling endosomes [40] in addition to the previously reported colocalization of Atg9 with the trans-Golgi network and other types of endosomes [26,85]. They also identified TBC1D14 in a screen for putative RabGAP proteins involved in autophagy.…”
Section: The Plasma Membrane and Recycling Endosomesmentioning
confidence: 85%